Exclusive e-cigarette use predicts cigarette initiation among college students. (January 2018) - Loukas, Alexandra; Marti, C. Nathan; Cooper, Maria; Pasch, Keryn E.; Perry, Cheryl L.
Abstract: Introduction: An increasing body of research indicates that use of electronic nicotine delivery systems (ENDS) predicts cigarette initiation. However, no studies examine if risk for cigarette initiation varies for exclusive ENDS users versus users of ENDS and other tobacco products. This study examined if: a) cigarette-naïve young adults (i.e., never cigarette users) who ever used ENDS had a greater odds of initiating cigarettes than non-ENDS users over a 1.5 year period and b) the odds of cigarette initiation was consistent across exclusive ENDS users and users of ENDS and at least one tobacco product. Methods: Participants were 2558 cigarette-naïve 18–25 year old ( M = 19.71; SD = 1.61) students from 24 Texas colleges who participated in a four-wave study, with six months between each wave. Results: Overall, 11% of students reported cigarette initiation by wave 4. Of those, 20.1% were wave 1 ENDS users and 8.4% were non-ENDS users. Multivariable, multilevel discrete-time hazard models indicated that wave 1 ENDS use predicted subsequent cigarette initiation, over and above the significant effects of cigarette use susceptibility, family-of-origin tobacco use, friend cigarette use, and other tobacco use. Additional findings indicated that exclusive ENDS users had a greater odds than non-users of subsequent cigarette initiation. Among users of alternative tobacco products, ENDS users did not have a greater odds of initiation than non-ENDS users. Conclusion: Findings extend existing research by showing that ENDS use by young adults is a specific risk factor for later cigarette initiation and not an extension of a constellation of existing tobacco use behaviors. Highlights: 11% of college students initiated cigarette use over the 1.5 year study period. More ENDS users than non-users initiated cigarette use during the study period. Exclusive ENDS use predicted subsequent cigarette initiation.